Harnessing windfall revenues: optimal policies for resource-rich developing economies - Frederick van der Ploeg; Anthony J. Venables (Center for Economic Studies and ifo Institute (CESifo), 2009)
A windfall of natural resource revenue (or foreign aid) faces government with choices of how to manage public debt, investment, and the distribution of funds for consumption, particularly if the windfall is both anticipated and temporary. We show that the permanent income hypothesis prescription of an ever-lasting increase in consumption financed by borrowing ahead of the windfall and then accumulating a Sovereign Wealth Fund (SWF) is not optimal for capital-scarce developing economies. Such countries should accumulate public and private capital to accelerate their development and, only if the windfall is large relative to initial foreign debt, is it optimal to build a SWF. The optimal time profile of consumption is biased towards the near future, as compared to the permanent income hypothesis. Outcomes depend on instruments available to government. We study cases where the government can make lump-sum transfers to consumers; where such transfers are impossible so optimal policy involves cutting distortionary taxation in order to raise investment and wages; and where Ricardian consumers can borrow against future revenues, in which case the policy response to possible over-consumption is a high level of investment in infrastructure.
Keywords: E60; F34; F35; F43; H21; H63; O11; Q33; 330; Natural resource revenue; windfall public revenues; risk premium on foreign debt; public infrastructure; private investment; credit constraints; optimal fiscal policy; debt management; Sovereign Wealth Fund; asset holding subsidy; developing economies; Rohstoffwirtschaft; Öffentliche Einnahmen; Windfall Profit; Staatsfonds; Finanzpolitik; Investitionspolitik; Debt Management; Theorie; Entwicklungsländer